Valence-bond theory of compounds of transition metals - Pauling, Linus (1975)
An equation relating the strength (bondforming power) of an spd hybrid bond orbital to the angles it makes with other bond orbitals is formulated and applied in the discussion of the structures of transition-metal carbonyls and other substances by the valence-bond method. The rather simple theory gives results that agree well with those obtained by the complicated and laborious calculation of sets of orthogonal hybrid bond orbitals with maximum strength.